ADAPTASI SOSIAL SANTRI DALAM MEMASUKI PENDIDIKAN DI PESANTREN MIFTAHUL ‘ULUM TANJUNGPINANG - Masyitah; Nanik Rahmawati; Rahma Syafitri (JURNAL SOSIO-KOMUNIKA, 2023)
Islamic boarding schools are one of the educational facilities for the community. In the pesantren environment, there are rules established by the foundation that must be obeyed by all students. For students who come from general education, when they enter the pesantren environment, they tend to experience differences such as the environment, rules, habits, and learning from the previous environment. When students face this, there are various responses from each student, starting from those who are used to experiencing it and those who have not experienced it at all. The purpose of this study is to find out what adaptation processes are experienced by students in entering the Miftahul 'Ulum Tanjungpinang Islamic boarding school environment. This study uses a qualitative descriptive approach, in determining the informants in this study based on a purposive sampling technique. The results of this study are that when students enter the pesantren environment, which originally came from general education, there is a process of social adaptation that occurs therein. Social adaptation with teaching staff, administrators, and other students, not only that in every environment there are binding rules that must be obeyed by individuals in it, especially new students to be able to adjust. This research concludes that every Santri is not always easy to go through the process of adaptation to the culture shock that arises from within and then needs to adjust to minimize this, the form of the stages of culture shock that occur; the individual feels happy and has hope for the future, the individual begins to experience obstacles in the new environment, the individual already knows and understands his environment and the individual is more accustomed to his new environment so that the process will have an impact on the next individual's life.